2022
DOI: 10.25035/jade.04.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Depressive Symptoms in NCAA Division III Collegiate Athletes

Abstract: Mental health disorders are important health concerns among collegiate athletes. Estimations of elevated depressive symptoms in this population range from 1.1-26%. However, these data are derived mostly from NCAA Division I institutions or professional athletes. Evidence from lower divisions (e.g., NCAA Division III) is currently sparse in the literature. Hence, the primary purpose of the present study was to examine the prevalence of depressive symptoms in NCAA Division III collegiate athletes. The secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Engaging in ball sports, strength sports and track and field was associated with more generalized anxiety symptoms. Fittingly, in a recent study, female sex was found to be a significant predictor of depressive symptoms, while age was not found to have significant predictive value (Wilson et al, 2022). In line with this, a meta-analysis showed that male elite athletes exhibited a 52% lower likelihood of reporting mild or severe depressive symptoms compared to their female counterparts who are also elite athletes (Gorczynski et al, 2017).…”
Section: Predictors Of Mental Health Symptomsmentioning
confidence: 84%
“…Engaging in ball sports, strength sports and track and field was associated with more generalized anxiety symptoms. Fittingly, in a recent study, female sex was found to be a significant predictor of depressive symptoms, while age was not found to have significant predictive value (Wilson et al, 2022). In line with this, a meta-analysis showed that male elite athletes exhibited a 52% lower likelihood of reporting mild or severe depressive symptoms compared to their female counterparts who are also elite athletes (Gorczynski et al, 2017).…”
Section: Predictors Of Mental Health Symptomsmentioning
confidence: 84%